Uporaba jezika italijanske narodne skupnosti v javni upravi - Pirnat, Tadeja (Javna uprava, 2017)
Autochthonous Italian National Community in the Republic of Slovenia (hereinafter referred to as RS) is guaranteed all rights under the Constitution RS and international treaties as provided for in the Basic Constitutional Charter on the Independence and Sovereignty of the Republic of Slovenia. Under the Slovenian legal and regulatory framework, the protection of the Italian National Community is covered mainly by sectoral laws (i.e. Law on Public Usage of Slovenian Language, State Administration law, The Law on Administrative Procedure etc.) and one Regulation on administrative procedures. The article addresses the usage of Italian language before public authorities, particularly the actual activity of administration offices, the organization of the Italian National Minority in Slovenia and the adversaries confronted when preserving national identity. The key purpose of this paper is to prove the need to repeatedly involve the Constitutional Court of the Republic of Slovenia to interpret the Constitution and the Public Sector Inspectorate - a body under the responsibility of the Ministry of Public Administration of the Republic of Slovenia; and low usage of the Italian language before the administrative bodies due to poor knowledge and/or complete lack of Italian documentation needed for administrative procedures. It seems that the Italian National Community members in spite of a sound regulatory framework, in preserving national identity, have to encounter numerous difficulties in order to ensure a treatment by the public authorities in accordance with the rule of law.
Keywords: Article 223 of Regulation on administrative procedures; articolo 223 del Regolamento sulla procedura amministrativa; Corte Costituzionale; Ispettorato del settore pubblico presso il Ministero della Pubblica Amministrazione; Italian language an official language in public administration; italijanska manjšina; javna uprava; Lingua italiana; manjšine; preservare l'identita nazionale; preserving national identity; Public Sector Inspectorate; Slovenija; the Constitutional Court; una lingua ufficiale dinanzi le autorita pubbliche; uporaba jezika; uradni jeziki